Identification of New X-Chromosomal Genes Required for Drosophila Oogenesis and Novel Roles for fs(1)Yb, brainiac and dunce - Swan, Andrew; Hijal, Sirine; Hilfiker, Andres; Suter, Beat

(untitled) (Genome Research, 2001)
We performed a screen for female sterile mutations on the X chromosome of Drosophila melanogaster and identified new loci required for developmental events in oogenesis as well as new alleles of previously described genes. We present mapping and phenotypic characterization data for many of these genes and discuss their significance in understanding fundamental developmental and cell biological processes. Our screen has identified genes that are involved in cell cycle control, intracellular transport, cell migration, maintenance of cell membranes, epithelial monolayer integrity and cell survival or apoptosis. We also describe new roles for the genesdunce (dnc), brainiac (brn) andfs(1)Yb, and we identify new alleles of Sex lethal(Sxl), ovarian tumor (otu), sans filles (snf), fs(1)K10, singed(sn), and defective chorion-1 (dec-1).